Hydrogen energy diaphragm with air tightness and ion transmission rate and preparation method

By using gradient mixed polyphenylene sulfide staple fibers and microfibers in the hydrogen-energy membrane and subjecting to hot pressing and hydrophilic treatment, the problem of easy shedding and short service life of the membrane coating is solved, and high airtightness and high ion transmission rate are achieved.

CN119711195APending Publication Date: 2025-03-28HUBEI XINRUN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411897954.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing polyphenylene sulfide diaphragm coating is prone to fall off, has a short service life, and is difficult to take into account good airtightness and high ion transfer rate.

Method used

By mixing polyphenylene sulfide staple fibers with polyphenylene sulfide microfibers in gradient proportions, a base cloth with gradient coating was prepared, and hot pressing and hydrophilic treatment were performed to produce a hydrogen-energy separator that had both airtightness and ion transfer rate.

Benefits of technology

The strength and service life of the diaphragm are improved, and the gradient structure optimization is achieved, and good airtightness and high ion transmission rate are achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a hydrogen energy diaphragm with air tightness and ion transmission rate and a preparation method, and belongs to the field of hydrogen production diaphragms. According to the preparation method, the polyphenylene sulfide short fibers are uniformly mixed in the pulp of the polyphenylene sulfide superfine fibers, the strength of the diaphragm is improved due to the addition of the polyphenylene sulfide short fibers, and the bonding effect between the coating and the base cloth is also improved due to the fact that the polyphenylene sulfide superfine fibers serve as a bonding agent, so that the finally prepared diaphragm is high in strength and long in service life. Meanwhile, by changing the content of the polyphenylene sulfide short fibers in the mixed slurry, the content of the polyphenylene sulfide short fibers in a mixed slurry coating layer close to the electrolyte is reduced, so that the coating layer is relatively small in pores, and the porosity is reduced; and the content of polyphenylene sulfide short fibers in the mixed slurry coating layer far away from the electrolyte is increased, so that the coating layer has relatively large pores, the porosity is improved, and the hydrogen energy diaphragm has good air tightness and relatively high ion transmission rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogen production membranes, and more specifically, relates to a hydrogen energy membrane having both air tightness and ion transmission rate and a preparation method thereof. Background Art

[0002] As the world pays more attention to energy transformation and low-carbon emission reduction, water electrolysis will play a more important role as a low-carbon and environmentally friendly hydrogen production method. The diaphragm is the core component and key material of the electrolyzer. It mainly serves to separate the cathode and anode chambers and the ion permeation, which directly affects the energy consumption and gas purity of the water electrolysis device.

[0003] Asbestos was the earliest material used for hydrogen production membranes by water electrolysis. Asbestos membranes were gradually replaced by polyphenylene sulfide (PPS) membranes due to their own shortcomings such as poor swelling and corrosion resistance. Polyphenylene sulfide membranes are heat-resistant, corrosion-resistant, and chemically stable, but they are hydrophobic and cannot fully contact the electrolyte, resulting in obstructed ion transmission and reduced electrolysis efficiency.

[0004] In order to overcome the influence of the hydrophobicity of the PPS diaphragm, the existing technology mainly prepares a composite diaphragm by coating a hydrophilic coating on the PPS diaphragm. Although the composite diaphragm improves the hydrophilicity of the PPS diaphragm to a certain extent, there is a problem with the stability of the coating material. If the bonding force between the PPS substrate and the coating material is weak, the coating material will fall off, resulting in a shortened life of the electrolyzer. In addition, the size and number of diaphragm pores have a significant impact on the ion transmission rate and air tightness. If the pore size is too large, although the ion transmission is smooth, the air tightness will decrease; if the pore size is too small, although the air tightness is good, the ion transmission is hindered. At present, it is difficult to take into account both good air tightness and a high ion transmission rate. Summary of the invention

[0005] In view of the defects of the prior art and the need for improvement, the present invention provides a hydrophilic hydrogen energy diaphragm and a preparation method and application, aiming to solve the technical problems of the existing polyphenylene sulfide diaphragm coating being easy to fall off, having a short service life, and being unable to achieve both good air tightness and a high ion transmission rate.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0007] (1) Weighing N groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers of different mass ratios, adding each group of polyphenylene sulfide staple fibers to the pulp of the corresponding polyphenylene sulfide superfine fibers, and mixing them evenly to obtain N groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries, wherein N ≥ 2, and the mass ratios of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers in the first group to the Nth group decrease in sequence;

[0008] (2) coating the first group of mixed slurries on both sides of the base fabric, and after drying, continuously coating the second group of mixed slurries on the surface of the first group of mixed slurries until the Nth group of mixed slurries are coated, and after drying, a base fabric with a gradient coating is obtained, wherein the base fabric is a polymer mesh fabric or a polymer woven fabric;

[0009] (3) The base fabric with the gradient coating obtained in step (2) is subjected to hot pressing and hydrophilic treatment to obtain a hydrogen energy diaphragm having both air tightness and ion transmission rate; wherein the hot pressing temperature is 80 to 250° C. and the hot pressing pressure is 1 to 10 MPa.

[0010] In a second aspect, the present invention provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0011] (1') weighing N groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers of different mass ratios, adding each group of polyphenylene sulfide staple fibers to the pulp of the corresponding polyphenylene sulfide superfine fibers, and mixing them evenly to obtain N groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries, wherein N ≥ 2, and the mass ratios of the polyphenylene sulfide staple fibers and the polyphenylene sulfide superfine fibers in the first group to the Nth group decrease in sequence;

[0012] (2') adding treatment agents to the N groups of mixed slurries obtained in step (1') to obtain N groups of mixed slurries of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide ultrafine fibers;

[0013] (3') coating a first group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry on both sides of the base fabric, and after drying, continuously coating a second group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry on the surface of the first group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry until the Nth group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry is coated, and after drying, a base fabric with a gradient coating is obtained, wherein the base fabric is a polymer mesh fabric or a polymer woven fabric;

[0014] (4') hot pressing the base fabric with gradient coating obtained in step (3') to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 80-250° C. and the hot pressing pressure is 1-10 MPa.

[0015] In a third aspect, the present invention provides a hydrogen energy diaphragm having both air tightness and ion transmission rate, wherein the hydrogen energy diaphragm is prepared by the preparation method described in the first aspect or the second aspect.

[0016] Furthermore, the diameter of the polyphenylene sulfide staple fiber is 2 to 30 μm, and the length is 10 to 100 mm; the diameter of the polyphenylene sulfide superfine fiber is 0.5 to 10 μm.

[0017] Furthermore, N=2, the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the first group is 1:1-0.01, and the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the second group is 0.01-1:1.

[0018] Furthermore, N=3, the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the first group is 1:1-0.01, the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the second group is 0.2-1:1, and the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the third group is 0.01-0.2:1.

[0019] Furthermore, the base fabric has a thickness of 50 to 300 μm, wherein the polymer constituting the base fabric includes one or more of polyphenylene sulfide and polyetheretherketone.

[0020] Furthermore, the base fabric is a polymer mesh fabric, the surface opening rate of the polymer mesh fabric is ≥25%, the mesh is an equilateral right triangle, and the right angle side length is 100 to 5000 μm; the polymer mesh fabric is woven from polymer single filaments, or polymer filament twisted double filaments, or polymer twisted yarns.

[0021] Furthermore, the surface opening rate of the polymer mesh cloth is 40-85%.

[0022] In a fourth aspect, the present invention provides a hydrogen production electrolyzer, comprising: a cathode, an anode and the hydrogen energy diaphragm as described in the third aspect.

[0023] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:

[0024] The present invention first weighs N groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers of different mass ratios, adds each group of polyphenylene sulfide staple fibers to the pulp of the corresponding polyphenylene sulfide superfine fibers, mixes them evenly, and obtains N groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries; then, the N groups of mixed slurries are sequentially coated on both sides of the base cloth, and after drying, hot pressing, and hydrophilic treatment, a hydrophilic hydrogen energy diaphragm is obtained. By uniformly mixing the polyphenylene sulfide staple fibers in the pulp of the polyphenylene sulfide superfine fibers, the strength of the diaphragm is improved due to the addition of the polyphenylene sulfide staple fibers, and the polyphenylene sulfide superfine fibers as a binder also improve the bonding effect between the coating and the base cloth, so that the finally prepared diaphragm has not only high strength but also long service life. At the same time, by changing the content of polyphenylene sulfide staple fibers in the mixed slurry, the content of polyphenylene sulfide staple fibers in the mixed slurry coating layer close to the electrolyte is reduced, so that the pores of the coating layer are smaller and the porosity is reduced; the content of polyphenylene sulfide staple fibers in the mixed slurry coating layer far away from the electrolyte is increased, so that the pores of the coating layer are larger and the porosity is improved, thereby ensuring that the hydrogen energy membrane has both good air tightness and a higher ion transmission rate. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0026] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0027] Example 1

[0028] This embodiment provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0029] (1) Weigh two groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers. The first group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 5 μm and 1.0 g of polyphenylene sulfide staple fibers with a diameter of 10 μm and a length of 50 mm. The second group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 5 μm and 0.01 g of polyphenylene sulfide staple fibers with a diameter of 10 μm and a length of 50 mm. The polyphenylene sulfide superfine fibers in the two groups are pulped respectively, and then each group of polyphenylene sulfide staple fibers is added to the pulp of the corresponding group of polyphenylene sulfide superfine fibers. The fiber disintegrator is used for dispersion and mixing. The mixing time is 1 hour. After the mixture is evenly mixed, it is dispersed in an aqueous solution with a mass fraction of 0.1% polyethylene oxide to obtain two groups of evenly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries.

[0030] (2) coating the first group of mixed slurries on both sides of the polyphenylene sulfide mesh cloth, and then coating the second group of mixed slurries after drying, and then drying again to obtain a polyphenylene sulfide mesh cloth with a gradient coating, wherein the polyphenylene sulfide mesh cloth has a thickness of 50 μm, is woven from polyphenylene sulfide single filaments, has a surface opening rate of 25%, and has a square mesh with a side length of 100 μm.

[0031] (3) The polyphenylene sulfide mesh cloth with gradient coating obtained in step (2) is subjected to hot pressing and vulcanization hydrophilic treatment to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 180° C. and the hot pressing pressure is 5 MPa.

[0032] The hydrogen energy diaphragm prepared in this embodiment has a porosity of 70.3%, an average pore size of 6.3 μm, a water contact angle of 5.3°, a breaking strength of 26.3 MPa, and a breaking elongation of 16.5%.

[0033] Example 2

[0034] This embodiment provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0035] (1) Weigh two groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers. The first group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 0.5 μm and 20 g of polyphenylene sulfide staple fibers with a diameter of 2 μm and a length of 10 mm. The second group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 0.5 μm and 0.5 g of polyphenylene sulfide staple fibers with a diameter of 2 μm and a length of 10 mm. The polyphenylene sulfide superfine fibers in the two groups are pulped respectively, and then each group of polyphenylene sulfide staple fibers is added to the pulp of the corresponding group of polyphenylene sulfide superfine fibers, and dispersed and mixed using a fiber disintegrator for 1.5 h. After mixing evenly, the mixed solution is dispersed in an aqueous solution of 0.13% polyethylene oxide by mass to obtain two groups of evenly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries.

[0036] (2) Coating the first group of mixed slurries on both sides of the polyetheretherketone mesh cloth, and then coating the second group of mixed slurries after drying, and then drying again to obtain a polyetheretherketone mesh cloth with a gradient coating, wherein the polyetheretherketone mesh cloth has a thickness of 150 μm, and the polyetheretherketone mesh cloth is woven from polyetheretherketone filaments and double filaments, has a surface opening rate of 40%, and has a square mesh with a side length of 1500 μm.

[0037] (3) The polyetheretherketone mesh cloth with gradient coating obtained in step (2) is subjected to hot pressing and vulcanization hydrophilic treatment to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 80° C. and the hot pressing pressure is 1 MPa.

[0038] The hydrogen energy diaphragm prepared in this embodiment has a porosity of 62.3%, an average pore size of 2.3 μm, a water contact angle of 4.1°, a breaking strength of 18.4 MPa, and an elongation at break of 14.2%.

[0039] Embodiment 3:

[0040] This embodiment provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0041] (1) Weigh two groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers. The first group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 10 μm and 100 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 100 mm. The second group is 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 10 μm and 1.0 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 100 mm. The polyphenylene sulfide superfine fibers in the two groups are pulped respectively, and then each group of polyphenylene sulfide staple fibers is added to the pulp of the corresponding group of polyphenylene sulfide superfine fibers, and dispersed and mixed using a fiber disintegrator for 2 hours. After uniform mixing, the mixed solution is dispersed in an aqueous solution of 0.2% polyethylene oxide by mass to obtain two groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries.

[0042] (2) Coating the first group of mixed slurries on both sides of the polyphenylene sulfide woven fabric, and then coating the second group of mixed slurries after drying, and then drying again to obtain a polyphenylene sulfide woven fabric with a gradient coating, wherein the thickness of the polyphenylene sulfide woven fabric is 300 μm, and the polyphenylene sulfide woven fabric is woven by a traditional weaving process, wherein the polyphenylene sulfide fibers are woven according to a specific warp and weft interlacing method.

[0043] (3) The polyphenylene sulfide woven fabric with gradient coating obtained in step (2) is subjected to hot pressing and vulcanization hydrophilic treatment to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 250° C. and the hot pressing pressure is 10 MPa.

[0044] The hydrogen energy diaphragm prepared in this embodiment has a porosity of 56.3%, an average pore size of 7.2 μm, a water contact angle of 7.8°, a breaking strength of 19.4 MPa, and a breaking elongation of 13.6%.

[0045] Example 4

[0046] This embodiment provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0047] (1) Three groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers were weighed. The first group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 20 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The second group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 0.5 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The third group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 0.01 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The polyphenylene sulfide superfine fibers in the three groups were pulped respectively, and then each group of polyphenylene sulfide staple fibers was added to the pulp of the polyphenylene sulfide superfine fibers in the corresponding group, and dispersed and mixed using a fiber disintegrator for 1 hour. After mixing evenly, the mixed liquid was dispersed in an aqueous solution with a mass fraction of 0.1% polyethylene oxide to obtain three groups of evenly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries.

[0048] (2) Coating the first group of mixed slurries on both sides of the polyetheretherketone mesh cloth, and then coating the second group of mixed slurries after drying, and then coating the third group of mixed slurries after drying, and then drying again to obtain a polyetheretherketone mesh cloth with a gradient coating, wherein the polyetheretherketone mesh cloth has a thickness of 150 μm, and the polyetheretherketone mesh cloth is woven from polyetheretherketone filaments and double filaments, with a surface opening rate of 40%, and a square mesh with a side length of 1500 μm.

[0049] (3) The polyetheretherketone mesh cloth with gradient coating obtained in step (2) is subjected to hot pressing and vulcanization hydrophilic treatment to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 80° C. and the hot pressing pressure is 1 MPa.

[0050] The hydrogen energy diaphragm prepared in this embodiment has a porosity of 61.5%, an average pore size of 2.1 μm, a water contact angle of 6.2°, a breaking strength of 26.3 MPa, and an elongation at break of 15.1%.

[0051] Example 5

[0052] This embodiment provides a method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, comprising the following steps:

[0053] (1') Three groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers were weighed. The first group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 20 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The second group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 0.5 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The third group consisted of 1.0 g of polyphenylene sulfide superfine fibers with a diameter of 1 μm and 0.01 g of polyphenylene sulfide staple fibers with a diameter of 30 μm and a length of 10 mm. The polyphenylene sulfide superfine fibers in the three groups were pulped respectively, and then each group of polyphenylene sulfide staple fibers was added to the pulp of the polyphenylene sulfide superfine fibers in the corresponding group, and dispersed and mixed using a fiber disintegrator for 1 hour. After mixing evenly, the mixed liquid was dispersed in an aqueous solution with a mass fraction of 0.1% polyethylene oxide to obtain three groups of evenly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries.

[0054] (2') Adding the treating agent nano zirconium oxide to the three groups of mixed slurries prepared in step (1') respectively to prepare three groups of mixed slurries of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide ultrafine fibers.

[0055] (3') coating both sides of the polyetheretherketone mesh cloth with a mixed slurry of a first group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers, and then coating with a mixed slurry of a second group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers after drying, and then coating with a mixed slurry of a third group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers after drying, and then drying again to obtain a polyetheretherketone mesh cloth with a gradient coating, wherein the polyetheretherketone mesh cloth has a thickness of 150 μm, is woven from polyetheretherketone filaments and twisted into double filaments, has a surface opening rate of 40%, and has a square mesh with a side length of 1500 μm.

[0056] (3) The polyetheretherketone mesh cloth with gradient coating obtained in step (2) is subjected to hot pressing treatment to obtain a hydrogen energy diaphragm having both air tightness and ion transmission rate; wherein the hot pressing temperature is 80° C. and the hot pressing pressure is 1 MPa.

[0057] The hydrogen energy diaphragm prepared in this embodiment has a porosity of 63.8%, an average pore size of 5.2 μm, a water contact angle of 5.4°, a breaking strength of 29.1 MPa, and an elongation at break of 18.2%.

[0058] Example 6

[0059] This embodiment provides a hydrogen energy diaphragm with both air tightness and ion transmission rate, which includes, from left to right: N layers of polyphenylene sulfide composite fibers, a layer of polymer mesh cloth or polymer woven fabric, and N layers of polyphenylene sulfide composite fibers; wherein N is an integer greater than or equal to 2, and each layer of polyphenylene sulfide composite fibers is composited with polyphenylene sulfide ultrafine fibers and polyphenylene sulfide staple fibers, and the closer the polyphenylene sulfide composite fibers are to the polymer mesh cloth or polymer woven fabric, the higher the content of polyphenylene sulfide staple fibers. The thickness of each layer of polyphenylene sulfide composite fibers is 20 to 200 μm; the diameter of polyphenylene sulfide staple fibers is 2 to 30 μm, and the length is 10 to 100 mm; the diameter of polyphenylene sulfide ultrafine fibers is 0.5 to 10 μm; the thickness of the polymer mesh cloth or polymer woven fabric is 50 to 300 μm. The thickness of the hydrogen energy diaphragm is 130 to 700 μm.

[0060] Example 7

[0061] This embodiment provides a hydrogen production electrolyzer, comprising: a cathode, an anode and a hydrogen energy membrane as described in Example 6.

[0062] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, characterized in that: The steps include: (1) Weighing N groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers of different mass ratios, adding each group of polyphenylene sulfide staple fibers to the pulp of the corresponding polyphenylene sulfide superfine fibers, and mixing them evenly to obtain N groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries, wherein N ≥ 2, and the mass ratios of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers in the first group to the Nth group decrease in sequence; (2) coating the first group of mixed slurries on both sides of the base fabric, and after drying, continuously coating the second group of mixed slurries on the surface of the first group of mixed slurries until the Nth group of mixed slurries are coated, and after drying, a base fabric with a gradient coating is obtained, wherein the base fabric is a polymer mesh fabric or a polymer woven fabric; (3) The base fabric with the gradient coating obtained in step (2) is subjected to hot pressing and hydrophilic treatment to obtain a hydrogen energy diaphragm having both air tightness and ion transmission rate; wherein the hot pressing temperature is 80 to 250° C. and the hot pressing pressure is 1 to 10 MPa.

2. A method for preparing a hydrogen energy diaphragm having both air tightness and ion transmission rate, characterized in that: The steps include: (1') weighing N groups of polyphenylene sulfide staple fibers and polyphenylene sulfide superfine fibers of different mass ratios, adding each group of polyphenylene sulfide staple fibers to the pulp of the corresponding polyphenylene sulfide superfine fibers, and mixing them evenly to obtain N groups of uniformly dispersed polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fiber mixed slurries, wherein N ≥ 2, and the mass ratios of the polyphenylene sulfide staple fibers and the polyphenylene sulfide superfine fibers in the first group to the Nth group decrease in sequence; (2') adding treatment agents to the N groups of mixed slurries obtained in step (1') to obtain N groups of mixed slurries of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide ultrafine fibers; (3') coating a first group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry on both sides of the base fabric, and after drying, continuously coating a second group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry on the surface of the first group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry until the Nth group of hydrophilic polyphenylene sulfide staple fibers / polyphenylene sulfide superfine fibers mixed slurry is coated, and after drying, a base fabric with a gradient coating is obtained, wherein the base fabric is a polymer mesh fabric or a polymer woven fabric; (4') hot pressing the base fabric with gradient coating obtained in step (3') to obtain a hydrogen energy diaphragm with both air tightness and ion transmission rate; wherein the hot pressing temperature is 80-250° C. and the hot pressing pressure is 1-10 MPa.

3. A hydrogen energy diaphragm having both air tightness and ion transmission rate, characterized in that: The hydrogen energy diaphragm is prepared by the preparation method as claimed in claim 1 or 2.

4. The hydrogen energy diaphragm according to claim 3, characterized in that: The diameter of the polyphenylene sulfide staple fiber is 2 to 30 μm, and the length is 10 to 100 mm; the diameter of the polyphenylene sulfide superfine fiber is 0.5 to 10 μm.

5. The hydrogen energy diaphragm according to claim 4, characterized in that: The N=2, the mass ratio of the polyphenylene sulfide staple fibers to the polyphenylene sulfide superfine fibers in the first group is 1:1-0.01, and the mass ratio of the polyphenylene sulfide staple fibers to the polyphenylene sulfide superfine fibers in the second group is 0.01-1:

1.

6. The hydrogen energy diaphragm according to claim 4, characterized in that: The N=3, the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the first group is 1:1-0.01, the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the second group is 0.2-1:1, and the mass ratio of polyphenylene sulfide staple fibers to polyphenylene sulfide superfine fibers in the third group is 0.01-0.2:

1.

7. The hydrogen energy diaphragm according to claim 3, characterized in that: The thickness of the base fabric is 50-300 μm, wherein the polymer constituting the base fabric includes one or more of polyphenylene sulfide and polyetheretherketone.

8. The hydrogen energy diaphragm according to claim 7, characterized in that: The base fabric is a polymer mesh fabric, the surface opening rate of the polymer mesh fabric is ≥25%, the mesh is an equilateral right triangle, and the right angle side length is 100-5000 μm; the polymer mesh fabric is woven from polymer single filaments, polymer filament double filaments, or polymer twisted yarns.

9. The hydrogen energy diaphragm according to claim 8, characterized in that: The surface opening rate of the polymer mesh cloth is 40-85%.

10. A hydrogen production electrolyzer, characterized in that: The hydrogen production electrolyzer comprises: a cathode, an anode and the hydrogen energy membrane as claimed in any one of claims 3 to 9.